A Research Agenda for Affective Dimensions in Climate Change Risk Perception and Risk Communication - Salas Reyes, Raúl; Nguyen, Vivian M.; Schott, Stephan; Berseth, Valerie; Hutchen, Jenna; Taylor, Jennifer; Klenk, Nicole (Frontiers in Climate, 2021)
There is a growing body of literature that examines the role of affect and emotions in climate change risk perception and risk communication. Conceptions of affect and emotions have differed according to theoretical perspectives and disciplinary orientations (e.g., sociology of risk, psychology of risk, climate science communication), but little has been done to map these differences. This perspective article provides an in-depth analysis of the study of affect and emotions in climate change risk research through a literature review of studies published in the last 20 years. In this perspective, we examined how affect is conceived, what emotions have been considered, and their role in climate change risk perception and risk communication. Early studies in climate risk perception and risk communication included vaguely defined emotions (e.g., negative and positive) in climate risk perception and risk communication studies, more recently turning attention to how different affective dimensions interact with other factors, such as personal experience, knowledge, culture and worldviews, gender, and social norms. Using this review as a mapping exercise of the research landscape on affect and emotions in climate risk perception and communication, we suggest that future research could benefit from more interdisciplinary work that explores the role of different affective responses and their intensities before, during, and after climate-related events.